Efeitos do extrato hidroalcoólico das folhas de Syzygium malaccense e Moringa oleífera sob estresse oxidativo em ratos diabéticos induzidos por estreptozotocina - Bicas, Thariane Carvalho (2019)
The specimens of Syzygium malaccenseand Moringa oleiferacultivated in Brazilian soil are sources of natural antioxidants. Phytotherapeutics has increasingly gained the academic community forits versatility, accessibility and ease of use as a food supplement. Your use of the traditional issue provides an investigation of your potential use of the therapeutic, its appreciation is related to composition, which contains an amount and class of compounds. Among the compounds, phenolic compounds play an important role in the inhibition processes of lipid peroxidation, inhibiting or reducing the capacity of oxidative stress. The reduction of oxidative stress, is associated to the improvement of several pathologies, among them diabetes. In this context, the present study was evaluated as the hydroalcoholiceffects of Moringa oleiferaand Syzygium malaccenseleaves on the biomarkers of oxidative stress in diabetic rats induced by streptozotocin. The production of the decorative extracts is better than the extraction coding for these cultures and the amount of material administered was determined according to the cell viability (MTT) method. The experimental model was evaluated by the determination of theactivity of antioxidant enzymes: catalase, glutathione s-transferase and non-protein thiols, as well as the determination of lipid peroxidation (TBARS) in the renal, hepatic and encephalic tissues of Wistar rats. The cell viability test showed that the dose of 500 mg / kg of extract for M. oleiferaand 400 mg / kg of S. malaccenseextract maintained cell integrity. There was a reduction in glycaemia in diabetic animals treated with plants.The lipid peroxidation in the evaluated tissues was decreased for both plants, however,the activity of antioxidant enzymes for renal and hepatic tissues was reduced only for the group of animals used with S. malacensein the experimental model. Animals isolated with M. oleiferashowed an improvement in the relationship as antioxidant enzymes only for renal tissue. However, this work demonstrated that a dose administered in the experimental model was not toxic to renal and hepatic tissues. Given these results, it is possible to suggest that plants under study are indicators of possible new therapeutic areas.